Sanitation in basic Schools - a case study in Tano-South District - Gyabaah, Daniel (2011)
A thesis submitted to The Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirement for the award of the Degree of Master of Science in Water Supply and Environmental Sanitation